Prevalence and comorbidity rates of disruptive mood dysregulation disorder in epidemiological and clinical samples: systematic review and meta-analysis - Xavier Benarous; Hélène Lahaye; Angèle Consoli; David Cohen; Réal Labelle; Jean-Marc Guilé (European Psychiatry)
Abstract